Impact of Climate Change on Agriculture Sector of Malaysia - Z., Mumuh Muhsin; Herlina, Nina; Falah, Miftahul; Saringendyanti, Etty; Sofianto, Kunto; Zin, Norlaila Md (International Journal of Energy Economics and Policy, 2021)
For the national economy, agriculture sector remains an important contributor in the national GDP with the provision of almost 16 percent employment. However, the problem of climate change is observed as a key challenge in the local market with its potential harmful effect on agriculture sector. The research task of this study is to test whether there is any relationship between climate change and agriculture sector of Malaysia. For research purpose, data was collected from different national and international databases during 1975-2015. Agriculture sector is defined with seven different factors and for the climate change, air pollution, greenhouse gas emission, and energy usage are added as main explanatory variables. Additionally, we tried to explore the effect of lagged predictors of explanatory variables on agriculture sector too. our results depict that there is mixed effect of climate change and energy usage on agriculture economy. However, none of the lag predictor is found to be a significant determinantal variable for agriculture dynamics in Malaysia. In the last, study results are recommended for ministry of agriculture and agro-based industry, and department of environment Malaysia for developing any type of acts, rules and regulations for the environmental quality and agro-based industry. It is suggested that future research contributions should definitely consider the other economies in ASEAN and Asian region for some getting some different facts with more generatability. Keywords: climate change, agriculture sector, Malaysia. JEL Classifications: Q54, N5, O13. DOI: https://doi.org/10.32479/ijeep.10939